2021
DOI: 10.3390/ijerph18178971
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Free Face Mask Distribution on Use of Face Masks. A Cluster Randomised Trial in Stovner District of Oslo, Norway

Abstract: Face masks are recommended as a means of reducing the spread of COVID-19, but there are practically no studies of interventions to increase face mask use. Over three weeks, nine grocery stores in the Stovner District of Oslo were randomly selected each day to have distribution of free face masks outside their entrance. Free face mask distribution increased the proportion of customers wearing a mask by 6.0 percentage points (adjusted, 95% CI 3.5–8.5). Mean mask usage was 91.7% in the control group and 97.1% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…Free mask distribution could encourage good mask-wearing behaviors. The finding supported the hypothesis proposed by Fretheim et al, who suggested that free distribution can increase face mask compliance [ 31 ]. Mask distribution can be regarded as social welfare to promote good mask-wearing behavior and combat the COVID-19 epidemic.…”
Section: Resultssupporting
confidence: 91%
“…Free mask distribution could encourage good mask-wearing behaviors. The finding supported the hypothesis proposed by Fretheim et al, who suggested that free distribution can increase face mask compliance [ 31 ]. Mask distribution can be regarded as social welfare to promote good mask-wearing behavior and combat the COVID-19 epidemic.…”
Section: Resultssupporting
confidence: 91%
“…Accordingly, Jefferson et al [ 5 ] discuss the lack of mask adherence as a possible cause of the inconclusive results of RCTs on the effectiveness of face masks in preventing ARIs. To increase the willingness to wear masks, public health authorities used social media to educate the public during the COVID-19 pandemic [ 30 ] or distributed masks free of charge [ 31 ]. In addition to these interventions, governments have introduced more drastic initiatives, such as mandatory masks, which penalize people who do not wear masks.…”
Section: Discussionmentioning
confidence: 99%